2004
DOI: 10.1136/oem.2004.012757
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of noise exposure in the Danish workplace: a baseline survey

Abstract: Aims: To evaluate an epidemiological approach to a national noise hazard surveillance strategy, and report current exposure levels in the Danish workplace. Methods: A study base of 840 companies in 10 selected high risk industries in the largest county in Denmark was identified from a national register. Noise exposure was measured among manual workers recruited from a random sample of workplaces in each industry. For reference, financial companies and a sample of residents were investigated according to the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 18 publications
1
28
0
Order By: Relevance
“…Unfortunately, at least in the case of noise, the exposures persist. Kock et al 47 reported that a substantial proportion of Danish industrial workers were exposed to noise levels above 85 dB(A). It is possible that physical workload has been substantially reduced in Western countries, but certainly not worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, at least in the case of noise, the exposures persist. Kock et al 47 reported that a substantial proportion of Danish industrial workers were exposed to noise levels above 85 dB(A). It is possible that physical workload has been substantially reduced in Western countries, but certainly not worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the levels of L eq found in this study, either by TBM (78.8e93.0 dBA) or full-day dosimetry (79.8e87.8 dBA) are higher, on average, than the levels found by Kock et al (2004) for many industries, revealing that fishermen of small and medium-scale fishing vessels are among the top workers exposed to occupational noise.…”
Section: Noise Exposure Levelsmentioning
confidence: 51%
“…5 Previous studies have suggested that use of hearing protection devices was higher with increasing noise exposure. 6,7 However, the effectiveness of hearing protection devices is influenced by numerous factors including proper training and use. 8 In this analysis, however, workplace size was provided using employer remuneration but not the actual number of workers by workplace.…”
Section: Discussionmentioning
confidence: 99%